2010
DOI: 10.1063/1.3380853
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependence of Si and Ge diffusion in relaxed Si1−xGex alloys

Abstract: Diffusion of silicon (Si) and germanium (Ge) in silicon-germanium Si1−xGex-isotope heterostructures with Ge contents x=0, 0.05, 0.25, 0.45, and 0.70 was investigated in a temperature range between 690 and 1270 °C. The concentration profiles of the stable Si-isotopes and Ge-isotopes were recorded by means of time-of-flight secondary ion mass spectrometry. Analysis of the experimental profiles shows that the Si and Ge diffusion coefficients in elemental Si agree within experimental accuracy. However with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 28 publications
6
72
0
Order By: Relevance
“…Since the electronic occupation and size of defects depend on charge states, the bowing of the defect formation energy should also be charge-dependent. Our theoretical model is consistent with experimental observations [24][25][26]. For examples, it is observed that Cu atoms accumulate in the mixed CdS x Te 1−x alloy region when small amount of S is mixed into CdTe at the CdTe/CdS interfaces in CdTe based solar cell [25].…”
supporting
confidence: 78%
“…Since the electronic occupation and size of defects depend on charge states, the bowing of the defect formation energy should also be charge-dependent. Our theoretical model is consistent with experimental observations [24][25][26]. For examples, it is observed that Cu atoms accumulate in the mixed CdS x Te 1−x alloy region when small amount of S is mixed into CdTe at the CdTe/CdS interfaces in CdTe based solar cell [25].…”
supporting
confidence: 78%
“…The Ge diffusion is very slow under strain free conditions 40,41 and seems to be enhanced by the growth mechanism as discussed in the following. The deposition of Si on Ge is governed by the 4.2% lattice mismatch between the two materials.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Interestingly, in previous experimental and theoretical studies it was shown than the structure and defect processes do not exhibit a Vegard law type behavior. 11,12 That is they cannot be determined by a simple linear interpolation of the respective properties of Si and Ge, which are the end members of Si 1-x Ge x . The deviations are typically larger for intermediate Ge contents, however, they can appear to be non-existent for very small or very large Ge contents.…”
Section: Introductionmentioning
confidence: 99%